MODERN TECHNOLOGIES IN TEACHING MATHEMATICS IN PRIMARY GRADES - Muxtorova Ra'no Turdibay qizi (Modern American Journals, 2025)
This study explores the application of modern technologies in teaching mathematics at the primary school level, with a particular focus on their effectiveness in enhancing pupils’ cognitive development, engagement, and problem-solving skills. Mathematics education in early grades forms the foundation for logical reasoning, analytical thinking, and future learning success. However, traditional teaching methods often struggle to meet the demands of 21st-century learners who are increasingly exposed to digital environments. The integration of modern educational technologies such as interactive whiteboards, digital learning platforms, gamification, adaptive software, and multimedia resources can transform the learning experience by fostering interactivity, visualization, and individualization. The research analyzes both theoretical perspectives and empirical findings from pilot studies conducted in selected schools. The methodology combines classroom observations, teacher interviews, and quantitative assessment of student progress. Results indicate that the use of interactive technologies significantly improves student motivation, supports differentiated instruction, and enhances comprehension of abstract mathematical concepts. Moreover, technology integration contributes to inclusive education by accommodating diverse learning styles and addressing special educational needs. Despite these advantages, challenges such as teacher training, resource availability, and digital literacy must be addressed for sustainable implementation. The findings of this study are intended to support policymakers, educators, and researchers in promoting evidence-based approaches to mathematics education in primary schools.